A review on water disinfection with plant products- - Humayun Wali; Muhammad Ahmed (Advances in Environmental Technology, 2023)
BackgroundConventional techniques for water disinfection are fraught with issues like personnel exposure to damaging radiation and formation of harmful and carcinogenic disinfection byproducts. There are difficulties related to transportation and handling, and expensive capital and working costs also are involved like costs associated with on-site generation of disinfectants. There is a dire need for newer disinfection technologies that are environment and health friendly.Scope and benefitsThis article reviews the use of natural disinfectants derived from plants to enhance the quality of water. Researchers have utilized herbal extracts, phytochemicals, and phytochemical-metal complexes for the disinfection of water. Various factors for these chemicals like efficacy, toxicity, cost, and water solubility have been discussed and some useful phytochemical disinfectants are also identified. These disinfection methods particularly when using only pure phytochemicals are generally thought to be free from the deleterious effects associated with chlorination and other conventional technologies. Inherently, chlorinated and other harmful disinfection byproducts are not formed.Key findings and conclusionsIn various studies eugenol, thymol and extracts of Ocimum sanctum and Azadirachta indica have been utilized with fairly effective disinfection capabilities. The significant antimicrobial effects of allicin, berteroin, sanguinarine, and thymol are reflected from their very low minimum inhibitory concentration values. Even so, presently the efficiency of phytochemicals is not comparable to conventional disinfectants. The use of phytochemical metal complexes is, however, a plausible option that might be investigated further. The metal complexes because of their greater water solubility than pure phytochemicals result in improved disinfection efficiency. Notable among those are flavonoid-metal complexes that should be considered further for use in water disinfection. It is also concluded that phytochemicals may be added to water that has also been disinfected with some other commonly-used technology. A way to do this may be to design a fixed bed tower of phyto-disinfectant through which water should pass.